Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1021/acs.energyfuels.0c03833
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Stratum Subsidence Induced by Depressurization at an Offshore Hydrate-Bearing Sediment

Abstract: Gas production from an offshore hydrate-bearing sediment (HBS) by depressurization will reduce the strength of cementation and increase the effective stress of hydrate reservoirs, which can result in some potential geohazards, such as wellbore instability and stratum subsidence. In this study, a thermal−hydrological−mechanical−chemical coupling numerical simulation model was established and applied in the example of the first offshore hydrate production test of Nankai Trough, Japan (2013). On the basis of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…There are six reviews covering a wide range of aspects related to methane hydrates targeting resource potential, production methods (depressurization and CH 4 /CO 2 exchange), exploration activities, sand management, and hydrate properties . The original research articles pertaining to the topic of hydrates cover a wide spectrum of areas, from numerical modeling, ,,, hydrate properties and characterization, ,,,, hydrate equipment ,,, to fluid production analysis, , ,, etc.…”
Section: Hydratementioning
confidence: 99%
“…There are six reviews covering a wide range of aspects related to methane hydrates targeting resource potential, production methods (depressurization and CH 4 /CO 2 exchange), exploration activities, sand management, and hydrate properties . The original research articles pertaining to the topic of hydrates cover a wide spectrum of areas, from numerical modeling, ,,, hydrate properties and characterization, ,,,, hydrate equipment ,,, to fluid production analysis, , ,, etc.…”
Section: Hydratementioning
confidence: 99%
“…There are three conventional NGH exploitation methods: depressurization, thermal stimulation, , and inhibitor injection, as well as the combined use of these three methods. Among them, depressurization is considered the most economical and effective exploitation method. , Many countries have formulated and implemented trial production of hydrate. , From 2007 to 2008, Japan and Canada conducted trial production of hydrate in the Mackenzie Delta area using a stepwise depressurization method . It was inferred that in the initial stage of depressurization, the gas production rate increased rapidly due to the permeability increase, but then, the gas production rate decreased due to the permeability decrease .…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that seabed subsidence would lead to a sharp decline in slope stability. Li et al 32 studied the subsidence variation in offshore reservoirs. The results showed that evident formation subsidence existed in near-well regions due to the combined action of hydrate decomposition and effective stress increase.…”
Section: ■ Introductionmentioning
confidence: 99%